RECALIBRATION OF THE SPHALERITE COSMOBAROMETER: EXPERIMENTAL AND THEORETICAL TREATMENT - Balabin A.I.; Urusov V.S. (My University, 1995)
Temperature dependence of the composition of sphalerite in equilibrium with troilite + metallic iron has been determined experimentally from 400 to 840°C at 1 bar. The high-temperature runs (660–840°C) were conducted in evacuated silica tubes; a new version of the recrystallization in anhydrous halide flux technique was used for attaining equilibrium at 600-400°C.The zero-pressure solvus of sphalerite proved to be at higher FeS contents than was located by Barton and Toulmin (1966). Detailed calculations, based on updated thermochemical appraisal of the sphalerite (Zn,Fe)S solution, have shown the new solvus to be in apparent consistency with the high-pressure experimental data of Hutchison and Scott (1983 ).An improved calibration of the cosmobarometer is presented, based on our experimental results and those of Hutchison and Scott (1983) ; the calibration takes into account some inferences regarding thermodynamic properties of sphalerite solution and low-temperature polymorphism in FeS.Recently published metallographic cooling rates of iron meteorites (Saikumar and Goldstein, 1988) provide estimates of blocking temperatures for Fe diffusion in sphalerite, which fall in the range 205–217°C. Pressures of formation of these meteorites calculated from available sphalerite compositions range from 0 for Landes to 1.8 kbar for Toluca. The most reliable of the pressure estimates exhibit a linear relationship with wt% Ni of the meteorite.